Use of the Six Sigma methodology for the preparation of parenteral nutrition mixtures - M. F. Silgado Bernal; I. Basto Benítez; G. Ramírez García (Farmacia Hospitalaria, 2014)
Abstract: Objective: To use the tools of the Six Sigma methodology for the statistical control in the elaboration of parenteral nutrition mixtures at the critical checkpoint of specific density. Methods: Between August of 2010 and September of 2013, specific density analysis was performed to 100% of the samples, and the data were divided in two groups, adults and neonates. The percentage of acceptance, the trend graphs, and the sigma level were determined. A normality analysis was carried out by using the Shapiro Wilk test and the total percentage of mixtures within the specification limits was calculated. Results: The specific density data between August of 2010 and September of 2013 comply with the normality test (W = 0.94) and show improvement in sigma level through time, reaching 6/6 in adults and 3.8/6 in neonates. 100% of the mixtures comply with the specification limits for adults and neonates, always within the control limits during the process. Conclusion: The improvement plans together with the Six Sigma methodology allow controlling the process, and warrant the agreement between the medical prescription and the content of the mixture.